The effect of removing hearing aids on postural sway in older adults with age-related hearing loss: an experimental study - Kolasa, Sylwia; Bogen, Bård; Nilsen, Roy M.; Goplen, Frederik; Nordahl, Stein Helge G.; Wilhelmsen, Kjersti Thulin; Berge, Jan Erik; Meldrum, Dara; Hernes, Susanne S.; Steihaug, Ole Martin; Magnussen, Liv H. (Frontiers in Aging Neuroscience, 2025)
BackgroundStudies show that there is an association between age-related hearing loss (HL) and balance in older individuals. Several studies have indicated that the use of hearing aids (HAs) may have a positive impact on balance. However, the effect of HAs on postural sway in standing is still debated and unclear. The aim of this study was to examine differences in postural sway with and without the use of HAs, and the association between hearing threshold on balance and controlling for confounders, when comparing the use of HAs to not using them.MethodsIn this study, balance was tested in standing position on a force platform in individuals ≥70 years (N = 50) with HL (>30 dB) under four conditions (on a firm surface with eyes open and closed, and on a foam surface eyes open and closed). Postural sway was registered with and without using HAs, and the difference between the two conditions was examined by paired sample t-test. Associations between postural sway and hearing threshold was examined separately with and without using HAs by multiple regression analysis.ResultsThere was a statistically significant reduced postural sway (better balance) on a firm surface with eyes open with an effect size of 0.43 (95% CI 0.15 to 0.73, p = 0.003) using HAs compared to not using them. Multiple regression analyses did not show any significant associations between postural sway and hearing threshold after adjustments for cofounding factors, including age, sex, education, diabetes, cardiovascular diseases, and dizziness.DiscussionIn this study, participants demonstrated significantly better balance when standing on a firm surface with eyes open while using HAs, compared to standing without them. However, this improvement was not observed when standing on foam surface. Further research is necessary to examine the impact of HAs on balance across various conditions and surfaces. Future studies should also investigate the underlying mechanisms of these effects, including how HAs may influence proprioception and postural control, particularly in environments that challenge balance, such as foam surfaces.